The Impact of the Russia and Ukraine War on Indonesian Economic and Trade Performance - Arif Darmawan; Nairobi Nairobi; Roby Rakhmadi; Ghania Atiqasani (Jurnal Ekonomi dan Studi Pembangunan, 2023)
The Russian military invasion of Ukraine surprisingly impacted the world's geopolitical situation. The conflict that started at the end of February is ongoing, potentially disrupting economic and trade performance in the global sector, including Indonesia. The battle has the opportunity to increase some food commodity prices, thus hampering the total imports carried out. In addition, other leading commodities (non-oil and gas) such as gold, oil, and coal will also experience significant turmoil due to the conflict that has continued to heat up recently. The study provides an overview of the systemic impact on Indonesia's economic conditions by predicting the short-term possibilities. This study investigates the Russia-Ukraine conflict's initial estimate of the net import value of the two countries and other trading partners. This study uses independent variables, namely oil and gas commodities and gold prices over eleven years (2000-2021). Error Correction Model (ECM) is an analytical method used in this study. This research expects to give an overview to academia, business, industry, and the government in anticipating Indonesia's economic and trade performance to the crisis in Russia and Ukraine. Thus, it is hoped that this research can be used as an illustration of the government to make decisions in allocating import values amid the polemic between Russia and Ukraine so that trade values can be optimal.